The coupled system response to 250 years of freshwater forcing: Last Interglacial CMIP6–PMIP4 HadGEM3 simulations - M. V. Guarino; M. V. Guarino; L. C. Sime; R. Diamond; J. Ridley; D. Schroeder (Climate of the Past, 2023)
The lig127k-H11 simulation of the Paleoclimate Modelling Intercomparison Project (PMIP4) is run using the HadGEM3-GC3.1 model. We focus on the coupled system response to the applied meltwater forcing. We show here that the coupling between the atmosphere and the ocean is altered in the hosing experiment compared to a Last Interglacial simulation with no meltwater forcing applied. Two aspects in particular of the atmosphere–ocean coupling are found to be affected: Northern Hemisphere (NH) gyre heat transport and Antarctic sea ice area. We apply 0.2 Sv of meltwater forcing across the North Atlantic during a 250-year-long simulation. We find that the strength of the Atlantic Meridional Overturning Circulation (AMOC) is reduced by 60 % after 150 years of meltwater forcing, with an associated decrease of 0.2 to 0.4 PW in meridional ocean heat transport at all latitudes. The changes in ocean heat transport affect surface temperatures. The largest increase in the meridional surface temperature gradient occurs between 40–50∘ N. This increase is associated with a strengthening of 20 % in 850 hPa winds. The jet stream intensification in the Northern Hemisphere in return alters the temperature structure of the ocean by increasing the gyre circulation at the mid-latitudes and the associated heat transport by +0.1–0.2 PW, and it decreases the gyre circulation at high latitudes with a decrease of ocean heat transport of −0.2 PW. The changes in meridional surface temperature and pressure gradients cause the Intertropical Convergence Zone (ITCZ) to move southward, leading to stronger westerlies and a more positive Southern Annual Mode (SAM) in the Southern Hemisphere (SH). The positive SAM influences sea ice formation, leading to an increase in Antarctic sea ice.